УСТАНОВКИ як ВАЖЛИВИЙ чинник ГОТОВНОСТІ МАЙБУТНІХ УЧИТЕЛІВ МУЗИКИ ДО МУЗИЧНО-ПРОСВГГНИЦЬКОЇ ДІЯЛЬНОСТІ У ШКОЛІ (Педагогіка вищої та середньої школи, 2007)
The definite types of the attitudes which promote the perfect level of conduction of musical-educational activities by the future teachers of music are considered in this article.